EXPLORING THE PERCEPTION, ISSUES, AND ADOPTION INTENTIONS OF E-BANKING SERVICES AMONG WOMEN CUSTOMERS IN KARNATAKA - Rajeshwari M; N. Gunasekaran (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the perception, challenges, and adoption intentions of e-banking services among women customers in Karnataka. E-banking has revolutionized the way financial services are accessed, offering convenience and efficiency. However, despite its growing popularity, certain segments of the population, especially women, face challenges in adopting these services. This research aims to understand the factors influencing women’s perceptions of e-banking, identify barriers they encounter, and assess their intention to adopt such services. Through a survey of women customers in various cities of Karnataka, this study seeks to provide insights into their attitudes towards e-banking and suggest ways to enhance its adoption among women. The findings of the study will help policymakers and financial institutions to tailor their strategies for improving e-banking services and increase accessibility for women customers.